Pengaruh Kepemilikan Institusional, Ukuran Perusahaan, Capital Intensity dan Leverage terhadap Manajemen Pajak - Putri Amanda; Theresia Hesti Bwarleling (Jurnal Multidisiplin Indonesia, 2026)
This study aims to examine the effect of Institutional Ownership, Firm Size, Capital Intensity, and Leverage on Tax Management in property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The study was conducted to evaluate the extent to which tax management practices are implemented to maintain corporate stability and fulfill responsibilities toward stakeholders.This research employs secondary data obtained from companies’ financial statements. The research sample was selected using the purposive sampling method and analyzed using SPSS version 29 with multiple linear regression analysis techniques. Tax Management is proxied by the Current Effective Tax Rate (Current ETR), Institutional Ownership by institutional ownership proportion, Firm Size by the natural logarithm of total assets, Capital Intensity (CIR), and Leverage (DAR). The simultaneous test results indicate that all independent variables significantly affect Tax Management. Partially, Firm Size and Capital Intensity do not significantly influence Tax Management, while Institutional Ownership and Leverage have a significant positive effect on Tax Management. The findings conclude that companies with higher levels of Institutional Ownership and Leverage tend to engage more actively in Tax Management practices.